Slow surface plasmon polaritons with a large normalized delay bandwidth product in an ultracompact metal gap superlattice - Li, Chunlei (2013)
We propose a metal gap superlattice that can decrease the group velocity of surface plasmon polaritons (SPPs) with a large normalized delay bandwidth product (NDBP) and small high-order dispersion. The length of the superlattice is only 8.60 μm and the transmission is 0.4. The multiple reflections of photons in the nanocavity result in slow SPP group velocity. The numerical analysis exploiting the transfer matrix method (TMM) is confirmed by the finite-difference time-domain (FDTD) numerical simulations. In addition, we also analyze the reason for pulse deformation.